Cough and reflux esophagitis in children: their co-existence and airway cellularity - Beem Christopher; Cleghorn Geoffrey J; Faoagali Joan; Cox Nancy C; Chang Anne B; Ee Looi C; Withers Geoffrey D; Patrick Mark K; Lewindon Peter J (BMC, 2006)
Abstract Background There are no prospective studies that have examined for chronic cough in children without lung disease but with gastroesophageal reflux (GER). In otherwise healthy children undergoing flexible upper gastrointestinal endoscopy (esophago-gastroscopy), the aims of the study were to (1) define the frequency of cough in relation to symptoms of GER, (2) examine if children with cough and reflux esophagitis (RE) have different airway cellularity and microbiology in bronchoalveolar lavage (BAL) when compared to those without. Methods Data specific for chronic cough (>4-weeks), symptoms of GER and cough severity were collected. Children aged <16-years (n = 150) were defined as 'coughers' (C+) if a history of cough in association with their GER symptoms was elicited before BAL were obtained during elective esophago-gastroscopy. Presence of esophagitis on esophageal biopsies was considered reflux esophagitis positive (E+). Results C+ (n = 69) were just as likely as C- (n = 81) to have esophagitis, odds ratio 0.87 (95%CI 0.46, 1.7). Median neutrophil percentage in BAL was significantly different between groups; highest in C+E- (7, IQR 28) and lowest in C-E+ (5, IQR 6). BAL positive bacterial culture occurred in 20.7% and were more likely present in current coughers (OR 3.37, 95%CI 1.39, 8.08). Airway neutrophilia (median 20%, IQR 34) was significantly higher in those with BAL positive bacterial cultures than those without (5%, 4; p = 0.0001). Conclusion In children without lung disease, the common co-existence of cough with symptoms of GER is independent of the occurrence of esophagitis. Airway neutrophilia when present in these children is more likely to be related to airway bacterial infection and not to esophagitis.